Effects of Conventional Exercise versus Functional Training on Physical Performance in AJA Students during the Socialization Course: A Quasi-Experimental Study - Omidi, Hamid; Sabzevari Rad, Reza; Shamlou kazemi, Amir (Health Nexus, 2025)
This study compared the effects of conventional exercise and functional training, implemented during the AJA socialization course, on multiple dimensions of physical performance. A quasi-experimental pre-test–post-test design was employed. Thirty-four male AJA students were randomly assigned to either a conventional exercise group (n = 17) or a functional training group (n = 17). Physical performance was evaluated using the 1-1-1 Army Physical Fitness Test (one-mile run, push-ups, sit-ups), the Running-based Anaerobic Sprint Test (RAST), and the Y-Balance Test (YBT). Paired-sample t-tests assessed within-group changes, and analysis of covariance (ANCOVA) examined between-group differences while controlling for baseline values. Statistical significance was set at p ≤ 0.05.  Between-group comparisons revealed no significant differences for the one-mile run (p = 0.385, η² = 0.06) or the YBT anterior reach (p = 0.093, η² = 0.07). The functional training group showed significantly greater improvements in YBT posteromedial (p = 0.022, η² = 0.16) and posterolateral (p = 0.001, η² = 0.27) reaches, total YBT score (p = 0.031, η² = 0.34), peak anaerobic power (p = 0.001, η² = 0.36), push-ups (p = 0.017, η² = 0.18), and sit-ups (p = 0.028, η² = 0.16).  Functional training produced greater improvements in anaerobic power, dynamic balance, and muscular endurance compared to conventional exercise during the AJA socialization course. Given its superior performance outcomes and potential to reduce musculoskeletal injury risk, functional training should be prioritized in military induction programs to better prepare recruits for advanced training and operational demands.